Geochemical characteristics of shale gas formation and the potential for carbon storage in Thailand: An example from the Triassic Huai Hin Lat Formation - Chenrai, Piyaphong; Assawincharoenkij, Thitiphan; Jitmahantakul, Sukonmeth; Chaiseanwang, Patthapong (Frontiers in Earth Science, 2022)
An evaluation of the potential shale gas play and geological carbon dioxide (CO2) storage from the Triassic Huai Hin Lat Formation in Thailand is performed based on field observation, mineralogical data and geochemical data. This study is mainly focused on mudstone samples in some parts of the Huai Hin Lat Formation. The samples can be divided into three groups based on their mineral compositions: coaly mudstone, carbonate-siliceous mudstone and carbonate mudstone. The brittleness index based on their mineral compositions indicates that the samples show ultra-high carbonate and quart contents suggesting a good hydraulic fracture candidate. Total organic carbon and extractable organic matter of the samples represent poor to excellent generation potential for petroleum source rock with type III kerogen. From the depositional environment, it can be interpreted that the Huai Hin Lat Formation occurs in an anoxic to suboxic condition in an aquatic depositional environment. The formation is suitable for geological CO2 storage, which may reduce the CO2 during petroleum production and increase production rate. Consequently, the results from this study are useful for the unconventional shale reservoir exploration and carbon storage technology in Thailand and adjacent countries.